Inhibitory Killer Immunoglobulin-like receptors to self HLA-B and HLA-C ligands contribute differentially to Natural Killer cell functional potential in HIV infected slow progressors - Kamya, Philomena; Tallon, Benjamin; Melendez-Pena, Carlos; Parsons, Matthew S.; Migueles, Stephen A.; Connors, Mark; Miconiatis, Sofia; Song, Rujun; Boulet, Salix; Bruneau, Julie; Tremblay, Cecile L.; Bernard, Nicole F. (Clinical immunology (Orlando, Fla.), 2012)
Inhibitory Killer Immunoglobulin-like Receptors (iKIR) interact with their ligands, HLA molecules, to license Natural Killer (NK) cells for functional competence. Previous studies stimulating peripheral blood mononuclear cells (PBMCs) with the HLA-devoid K562 cell line revealed that NK cells from individuals with an iKIR encoded by the KIR3DL1 locus with self HLA-Bw4 as their ligands, had higher frequencies of tri-functional NK cells that expressed the degranulation marker CD107a and secreted Interferon-γ and Tumor Necrosis Factor-α than those from individuals who were homozygous for HLA-Bw6 alleles, which are not ligands for these iKIR. To assess the effect of other iKIR to self-HLA (S-iKIR) on the NK cell response, we compared HIV-infected slow progressors (SP) carrying S-iKIR to HLA-C alleles with or without S-iKIR to HLA-Bw4. We show that S-iKIR to HLA-B and C alleles differ in their contribution to NK cell functional potential in HIV-infected SP upon stimulation with K562 targets. ► HLA antigens bind inhibitory Killer immunoglobulin-like receptors (iKIR). ► HLA and iKIR interact to license NK cells for functional competence. ► The impact of iKIR to self HLA-B and C was compared in HIV+ and HIV- subjects. ► S-iKIR to HLA-C contribute little to NK function in HIV infected slow progressors. ► S-iKIR to both HLA-B and HLA-C contribute to NK function in uninfected subjects.